2022
DOI: 10.3389/fpsyg.2022.1002665
|View full text |Cite
|
Sign up to set email alerts
|

How did lockdown and social distancing policies change the eating habits of diabetic patients during the COVID-19 pandemic? A systematic review

Abstract: BackgroundAfter the declaration of the COVID-19 pandemic, governments established national lockdowns and social distancing as an effective plan to control this disease. As a result of the lockdown policies, diabetic patients` access to food products, medication, and routine follow-ups is disrupted, making it difficult for them to control their disease.MethodsInternational databases, including PubMed/Medline, Web of Science, and Scopus, were searched until April 2022. All observational studies included assessin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Given that most disease transmission occurs among family members, friends, colleagues, and neighbors, which has been observed during various pandemics [9][10][11], the presence of infection cues indicates an increased likelihood of infection [12]. Preventive behaviors involve voluntary actions to avoid infection during an influenza pandemic [13], such as hygiene behaviors, mask wearing, social distancing, and uptake of vaccinations [14]. Empirical research has suggested that infection cues promote the adoption of preventive behaviors [15,16].…”
Section: Covid-19 Infection Cues and Preventive Behaviorsmentioning
confidence: 99%
“…Given that most disease transmission occurs among family members, friends, colleagues, and neighbors, which has been observed during various pandemics [9][10][11], the presence of infection cues indicates an increased likelihood of infection [12]. Preventive behaviors involve voluntary actions to avoid infection during an influenza pandemic [13], such as hygiene behaviors, mask wearing, social distancing, and uptake of vaccinations [14]. Empirical research has suggested that infection cues promote the adoption of preventive behaviors [15,16].…”
Section: Covid-19 Infection Cues and Preventive Behaviorsmentioning
confidence: 99%
“…A study by Riad et al 7 reported that emotional instability, stress, anxiety, trauma, and depression are commonly observed after the war and are more prevalent in children and adolescents. 8,9,11,12 Second, pressures from a new school, country, and culture and being away from his family and friends developed emotional stress for our patient. A study by Foo et al 13 mentioned that adapting to new environments and cultural practices can lead to significant stress levels, which in turn is related to manifestations of mental disorders.…”
Section: Discussionmentioning
confidence: 94%
“…A study by Riad et al 7 reported that emotional instability, stress, anxiety, trauma, and depression are commonly observed after the war and are more prevalent in children and adolescents. 8,9,11,12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations